MODEL OF ASSISTANCE IN THE REVIEW COMMUNITY IN EARLY DETECTION OF NON-CONNECTED DISEASES (NCD) AT AKBAR ISLAMIC FOUNDATION SAKO PALEMBANG - Azwaldi, Azwaldi; Agustin, Ismar; Erman, Imelda (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The prevalence of PTM in Indonesia has shown an increase when compared to Riskesdas 2013, including cancer, stroke, chronic kidney disease, diabetes mellitus and hypertension. The prevalence of cancer rose from 1.4% (Riskesdas 2013) to 1.8%; the prevalence of stroke rose from 7% to 10.9%; and chronic kidney disease rose from 2% to 3.8%. Based on blood sugar examination, diabetes mellitus rose from 6.9% to 8.5%; and the results of blood pressure measurement, hypertension increased from 25.8% to 34.1%. Increasing the pattern of behavior for Early Detection of Non-communicable Diseases (PTM) for the community is obliged to reduce the number of cases of disease and complications that occur, especially in the Community Recitation at the Grand Mosque of the Sako Palembang Islamic Foundation. Through mentoring activities for Early Detection of Diseases. Through efforts to examine risk factors such as blood pressure, body mass index (BMI), abdominal circumference, blood sugar levels (GDS), uric acid and cholesterol as well as education by distributing non-communicable disease leaflets. The results of the average age is 60.06 years, the BMI value obtained the average value is 23.0673, the GDS value for diabetes is 10.6% while non-diabetic is 89.4%, systolic blood pressure is 55.3% hypertension and diastolic blood pressure by 17.7% hypertension, abdominal circumference 31.2% abnormal and 4.2% normal and 64.5% not measuring the results of uric acid examination by 14.2% abnormal, 27.7% normal and 58.1% were not tested for uric acid with a PTM risk questionnaire. The results obtained from 41 who filled out the questionnaire were 6.4% with medium risk, 17.7% with slightly increased risk and 5% with low risk. Assistance activities for early detection of PTM risk factors are very necessary for the community to always remind them of their health and various threats to their health through various risk factors.